Microbial-induced CaCO3 filled seaweed-based film for green plasticulture application. (20th October 2018) - Abdul Khalil, H.P.S.; Chong, E.W.N.; Owolabi, F.A.T.; Asniza, M.; Tye, Y.Y.; Tajarudin, H.A.; Paridah, M.T.; Rizal, S.
Abstract: This work aimed to develop green biodegradable film using red seaweed ( Kappaphycus alvarezii ) as a base matrix and calcium carbonate (CaCO3 ) as a filler to enhance the properties of the red seaweed material for plasticulture purpose. CaCO3 which was produced by microbially induced precipitation (MB-CaCO3 ) using Bacillus sphaericus, was characterized and compared with the commercial CaCO3 (CCaCO3 ). FESEM image revealed that the size of MB-CaCO3 was smaller and more uniform compared to CCaCO3 . FTIR and XRD analyses confirmed the existence of crystalline polymorph of calcite in MB-CaCO3, which contained a higher percentage of calcite than CCaCO3 . However, the crystallinity and thermal stability of MB-CaCO3 was lower than CCaCO3 . From the results of physical, mechanical and thermal properties of composite films filled with CCaCO3 and MB-CaCO3 fillers, the optimum loading of CCaCO3 and MB-CaCO3 was found at 0.1% and 0.15%, respectively. Composite films filled with MB-CaCO3 promote brighter film, better water barrier, hydrophobicity and biodegradability compared to CCaCO3 . Since the effect of MB-CaCO3 on film functional properties was comparable to CCaCO3, it can be used as an alternative to CCaCO3 as inorganic filler for composite films in agriculture applications. Graphical abstract: Image 1 Highlights: A novel biodegradable composite film was prepared from red seaweed and CaCO3 . CaCO3 was produced by microbial-induced calcite precipitation method (MB- CaCO3 ). MB-CaCO3 exhibited different characteristics than the commercial CaCO3 . Effects of MB-CaCO3 on seaweed film properties was comparable to commercial CaCO3 . The developed composite films can be used as soil biodegradable mulch film.